Exploring endolysin-loaded liposomes for a transtympanic treatment of S. pneumoniae otitis media - Silva, Maria Daniela (2022)
Otitis media, the main reason for which antibiotics are prescribed in childhood, is often caused by Streptococcus pneumoniae. The exogenous use of recombinantly produced endolysins, peptidoglycan hydrolases encoded by bacteriophages at the end of their lytic cycle, have been shown to be very effective against this pathogen. To increase bioavailability, and consequently reduce the probability of a recurrent or chronic infection, endolysins could be applied topically in the ear. However, delivery systems with permeation enhancing characteristics are needed to surpass the barrier provided by the tympanic membrane, which separates the ear canal from the middle ear. Therefore, this work aimed to develop a novel delivery system for a transtympanic treatment of pneumococcal otitis media using endolysins. The MSlys endolysin was encapsulated into deformable liposomes composed of L-alpha-lecithin and sodium cholate (L:SC:MSlys) or PEG2000 PE (L:PEG:MSlys) with a efficiency of approximately 35% in average, being released in a controlled manner. Liposomes loaded with MSlys showed no cytotoxicity against keratinocyte and fibroblast cell lines. Moreover, MSlys-loaded liposomes interacted with S. pneumoniae cells, being able to significantly reduce planktonic and biofilm cells. Transtympanic permeation studies demonstrated that PEGylated liposomes significantly enhanced the transport of MSlys through human tympanic membranes in an ex vivo model, showing antipneumococcal effect after 2 hours. Nevertheless, degradation of MSlys occurred during extended incubation at 37 ºC, which affected its effectiveness. In conclusion, endolysin-loaded liposomes are a promising approach for transtympanic treatment of otitis media caused by S. pneumoniae. Nevertheless, further optimization is required in order to increase effectiveness.